Analysis of the Application of Problem-Based Learning Model on Critical Thinking Skills in Thematic Learning of Grade V Students of Mis Al-Ikhwah Pontianak - Azlansyah A (Universitas Pendidikan Indonesia (UPI), 2023)
The lack of students' critical thinking skills and understanding in learning occurs because the variations in learning models implemented by teachers have not been maximized, even though teachers apply other learning models, in their implementation the variations in learning models implemented so far have not been effective. The purpose of this research is to analyze the application of the Problem Based Learning model to students' critical thinking skills in thematic learning in class V of SD MIS Al-Ikhwah Pontianak. This research uses qualitative research, in which the researcher makes observations and observes the actions of the informant. The data collection techniques used were observation, interviews and documentation. The research results show that the application of the PBL (Problem Based Learning) learning method in the teaching and learning process really helps students to improve students' critical thinking skills as evidenced by the increase in student learning outcomes of 95.44%. This is because the application of the PBL learning method makes it easier for students to understand the material taught by the teacher, makes students active, confident and more courageous in answering questions given by friends between groups.